Working women in exile. Patterns and strategies of labour insertion by women from the Spanish republican exile in France and Mexico (1936-1945) - Negrete Peña, Rocío (Cuadernos de Historia, 2023)
This article presents a transnational comparison of the different public policies and individual strategies in the labour market insertion of women exiled after the Spanish Civil War (1936-1945) in the two main host countries: France and Mexico. In recent years, studies based on documentary sources or oral interviews from Mexico have shed light on the history of female exile in these terms, a task that is continuing in the French case. The aim of this research is to define the possibilities of insertion and the link with work of Spanish women in both countries, comparing the incidence of material conditions, exiled labor management policies and gender issues.